Evolution and Characterization of Zirconium 702 alloy at various temperatures - J. Lade; B. Dharavath; A. Badrish; S. Kosaraju; S.K. Singh; K.K. Saxena (Archives of Metallurgy and Materials, 2023)
The Zirconium 702 alloy effectively used in nuclear industry at various critical conditions like high temperature and high pressure. This survey is an assessment of insights into the mechanical properties of the metal when exposed to different temperatures along the rolling direction.The main objective of this work is to characterize the tensile properties, and fracture study of broken tensile test samples at various temperatures.The tensile samples tested in our current work are 100°C,150°C, and 200°C temperatures in different directions (0°, 45°, 90°) along with the rolling direction of the sheet. It is evident from the experimental results that temperatures significantly affect material properties. Temperature increases cause % elongation to increase, and strength decreases. ANOVA analysis revealed that temperature significantly influenced ultimate tensile strength (UTS), and yield strength (YS), as well as % elongation.The temperature contribution for UTS, YS, and % elongation is 41.90%, 31.60%, and 77.80% respectively. SEM fractured images showing the ductile type of behavior for all the temperatures.